Long term outcome of patients with gastric marginal zone B cell lymphoma of mucosa associated lymphoid tissue (MALT) following exclusive Helicobacter pylori eradication therapy: experience from a large prospective series. Issue 1 (18th December 2003) - Fischbach, W; Goebeler-Kolve, M-E; Dragosics, B; Greiner, A; Stolte, M
Abstract : Background: Helicobacter pylori plays a decisive role in the pathogenesis of gastric marginal zone B cell lymphoma of mucosa associated lymphoid tissue (MALT), and eradication therapy has become a widely accepted initial treatment of stage I disease. Objective: To determine the long term outcome of patients undergoing exclusive H pylori eradication therapy. Design: A prospective series of patients with newly diagnosed marginal zone B cell lymphoma of MALT. Setting: Multicentre study in Germany and Austria. Patients: Ninety five patients; 90 of these (five lost to follow up) with a mean age of 54.3 (27–85) years were followed up for at least 12 months. Intervention: Complete staging work up revealing stage I disease and H pylori infection. Patients received triple therapy (OMC: omeprazole 20 mg twice daily, metronidazole 400 mg twice daily, and clarithromycin 250 mg twice daily; or OAC: omeprazole 20 mg twice daily, amoxycillin 1000 mg twice daily, and clarithromycin 500 twice daily) for one week. Results: Median follow up was 44.6 (12–89) months. H pylori was successfully eradicated in 88 patients (98%); in two patients eradication therapy failed. Long term outcome was characterised by complete regression of lymphoma in 56 patients (62%), minimal residual disease in 17 patients (18%), partial remission in 11 patients (12%), no change in four patients (4%), and progressive disease in two patients (2%). Four patients with complete remission relapsed after 6, 8, 8, and 15 months, one revealing reinfection by H pylori . Regression rate was higher in stage I1 disease compared with stage I2, as diagnosed by endoscopic ultrasound. Conclusion: The majority of patients with low grade gastric MALT lymphoma treated by exclusive H pylori eradication have a favourable long term outcome, offering a real chance of cure.